2012
DOI: 10.1111/j.1476-5381.2012.02103.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of statins plus LDL receptor‐targeted liposome‐encapsulated doxorubicin increases in vitro drug delivery across blood–brain barrier cells

Abstract: BACKGROUND AND PURPOSEThe passage of drugs across the blood-brain barrier (BBB) limits the efficacy of chemotherapy in brain tumours. For instance, the anticancer drug doxorubicin, which is effective against glioblastoma in vitro, has poor efficacy in vivo, because it is extruded by P-glycoprotein (Pgp/ABCB1), multidrug resistance-related proteins and breast cancer resistance protein (BCRP/ABCG2) in BBB cells. The aim of this study was to convert poorly permeant drugs like doxorubicin into drugs able to cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 49 publications
0
49
0
Order By: Relevance
“…2,3,6 The activation of RhoA and RhoAK is known to enhance the Pgp activity in BBB cells. 11 It is not known: (1) whether the Wnt/RhoA/ RhoAK axis controls also the Pgp expression; (2) whether the canonical and non-canonical Wnt pathways cooperate in regulating the Pgp levels in BBB cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,3,6 The activation of RhoA and RhoAK is known to enhance the Pgp activity in BBB cells. 11 It is not known: (1) whether the Wnt/RhoA/ RhoAK axis controls also the Pgp expression; (2) whether the canonical and non-canonical Wnt pathways cooperate in regulating the Pgp levels in BBB cells.…”
Section: Discussionmentioning
confidence: 99%
“…The permeability to dextran-fluorescein isothiocyanate (molecular weight 70 kDa), [ 14 C]-inulin (molecular weight range: 5.0 to 5.5 kDa; 10 mCi/mmol; PerkinElmer), sodium fluorescein (molecular weight: 376.27 Da) was taken as a parameter of tight junction integrity 11,15 and measured as previously reported. 6,16 To measure the permeability coefficient of doxorubicin across the BBB monolayer, wild-type or RhoA-silenced hCMEC/D3 cells were grown for 7 days up to confluence in 6-multiwell Transwell devices, and treated as reported under the Results section.…”
Section: Permeability Assays Across Blood-brain Barriermentioning
confidence: 99%
See 2 more Smart Citations
“…The multidrug transporters (ABC transporters) are present in a number of normal tissues with barrier functions (18)(19)(20)(21)(22)(23), and may modulate the absorption of orally administered cytotoxic compounds. For example, ABCG2 is expressed mainly in the placenta, and it is indicated that ABCG2 may control the penetration of drugs from the maternal plasma into the fetus, thus protecting the fetus against the potential toxicity of the drugs (24).…”
Section: Discussionmentioning
confidence: 99%